Dekalog polityczny 1989–1995 Gustawa Herlinga-Grudzińskiego na podstawie Dzienników pisanych nocą - Fiktus, Paweł (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
At the moment of political change – political system after 1989. Environmental emigration joined the discourse on the evolution and regarding the Polish political scene. One of them was Gustav Herling-Grudzinski – longtime collaborator George Giedoryc and Literary Institute located in the Paris suburb of Maisons-Laffitte, the author of Another world. In his Diaries written at night included not only regarding literature or also called to the culture, but also referred to the political phenomena that then occurred. Much space is devoted to criticism of Polish political scene, vividly engaging in commenting on the changes taking place after losing an election by Lech Wałęsa – then president of Poland and winning Alexander Kwaśniewski – derived from the former Polish United Workers Party. After winning for the second presidential election he formulated his political Decalogue contains important comments on the Polish political class and the changes taking place after a period of transition. That was the end of his policy considerations presented Diaries written at night, because to political issues Gustav Herling-Grudzinski, returned only occasionally.
Keywords: Giedroyc, Jerzy (1906-2000); Herling-Grudziński, Gustaw (1919-2000); Kultura (czasopismo; Francja; 1947-2000); Instytut Literacki; Maisons-Laffitte; transformacja ustrojowa